Searching for natural conductive fibrous structures via a green sustainable approach based on jute fibers and silver nanoparticles - Ferreira, Diana (2018)
This paper provides new insights regarding jute fibers functionalization with silver nanoparticles (Ag NPs) with improved conductivity values and highlights the sustainability of the processes involved. These NPs were applied onto jute fabrics by two different sustainable methods: ultraviolet (UV) photoreduction and by using polyethylene glycol (PEG) as a reducing agent and stabilizer. Field Emission Scanning Electron Microscopy (FESEM) images demonstrated that the Ag NPs were incorporated on the jute fibers surface by the two different approaches, with sizes ranging from 70 to 100 nm. Diffuse reflectance spectra revealed the plasmon absorption band, corresponding to the formation of metallic Ag NPs, in all samples under study. Attenuated Total Reflectance-Fourier Transform Infrared Spectroscopy (ATR-FTIR) was used to characterize the obtained samples, demonstrating NPs adsorption to the surface of the fibers. The resistivity value obtained by the two-point probe method of the jute fabric without functionalization is about 1.5 × 107 Ω·m, whereas, after NPs functionalization, it decreased almost 15,000 times, reaching a value of 1.0 × 103 Ω·m. Further research work is being undertaken for improving these values, however, 1000 Ω·m of resistivity (conductivity = 0.001 S/m) is already a very reasonable value when compared with those obtained with other developed systems based on natural fibers. In summary, this work shows that the use of very simple methodologies enabled the functionalization of jute fibers with reasonable values of conductivity. This achievement has a huge potential for use in smart textile composites.